Read the explanation box before answering since it might confuse you.
24a^-2 times b^3
12a^4 times b^-2
The divided by part is supposed be a division bar with the top being the numerator and the bottom being the demoninator.
1 Answer | Add Yours
You need to simplify the following expression such that:
You need to use negative power property such that:
`a^(-2) = 1/a^2`
`b^(-2) = 1/b^2`
`(24*b^3/a^2)/(12a^4/b^2) = (24/12)(b^3/a^2)*(b^2/a^4)`
Using exponential identities yields:
`(24*a^(-2)*b^3)/(12a^4*(b^-2)) = 2*(b^(3+2))/(a^(2+4))`
`(24*a^(-2)*b^3)/(12a^4*(b^-2)) = 2b^5/a^6 = 2a^(-6)b^5`
Hence, simplifying the given expression yields `(24*a^(-2)*b^3)/(12a^4*(b^-2)) = 2a^(-6)b^5.`
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes